Addiction and Pastoral Care - Waters, Sonia E. (Wm. B. Eerdmans Publishing Co., 2019)
Intro -- Title Page -- Copyright -- Contents -- Foreword by John Swinton -- Acknowledgments -- Introduction -- Addiction across the Board -- Addiction Organized -- Terms and Conditions -- 1. Addiction as Soul-Sickness -- Addiction, Relationality, and Soul-Sickness -- How We See Addictions: A Brief History -- Limits of the Moral and Medical Models -- The Emergence of Addiction -- Symptoms of the Sickness -- Desire, Pleasure, and Soul-Sickness -- The Framework of a Soul-Sickness -- 2. This Is Your Brain on Drugs -- Drugs Inside and Outside the Self -- The Rewiring of the Brain -- "Your Mind Is an Unsafe Neighborhood -- Don't Go There Alone" -- The Progress into Possession -- Chronic Stress in Addiction -- Excursus: Porn Addiction -- The Brain in Pastoral Care -- 3. Addiction, Attachment, and Trauma -- Attachment and Self-Regulation -- Resistant, Avoidant, and Disorganized Attachment Relationships -- Childhood Trauma and Disorganized Attachment -- Post-traumatic Stress Disorder -- Excursus: Eating Disorders -- Putting the Pieces Together -- Christian Practices of Self-Regulation -- A Slower Resurrection -- 4. Addiction and Social Suffering -- Racism, Homophobia, and Distress -- Social Stress and the Crossover Effect -- Socioeconomic Insecurity -- The War on Drugs -- Social Sin in Pastoral Care -- 5. Soul-Sickness and the Legion -- The Social Demoniac -- Bargaining with a Demon -- Healing and Restoration -- The Soul in Soul-Sickness -- Untangling the Demoniac from God -- Meaning-Making through Moral Complexity -- Incarnational Grace -- 6. Motivational Interviewing and Change -- The Balancing Act of Change -- Intrinsic Motivation and Cultural Values -- FRAMES Brief Intervention -- FRAMES Feedback and the "Elicit-Provide-Elicit" Model of Intervention -- Excursus: The Loved Ones of a Legion -- Pastoral Care and the Self -- 7. Moving into Change.